The Shaping of CBBE Based on Customer Experience, Product Features, and Digital Information - Purwandari, Fani Mutyaning; Rufaidah, Popy (International Research Journal of Business Studies, 2025)
This study originates from a question regarding what shapes brand strength in the minds of customers, particularly in the context of mortgage products (KPR) offered by bank. Customer experience, product features, and digital information are considered key interrelated factors. The study involved 100 mortgage customers of bank and employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that customer experience and product features have a strong influence on customer-based brand equity (CBBE), while digital information did not show a significant direct effect. Product features such as competitive interest rates and an easy application process were found to play a dominant role in shaping brand perception. Furthermore, customer experience influences CBBE indirectly through perceptions of product features. These findings emphasize that brand building is not solely about promotion, but also about delivering real customer experiences, offering clear product value, and implementing effective digital communication strategies.